Phrenic Nerve Paralysis: Effects on Diaphragm Mobility (London Journal of Medical and Health Research, 2025)
Phrenic nerve paralysis is a severe clinical condition with significant repercussions on respiratory mechanics and patient quality of life. It results from the interruption of diaphragmatic innervation, compromising the physiology of the muscle, reducing pulmonary expansion, and leading to alveolar hypoventilation. The phrenic nerve originates from the cervical roots C3 to C5, following a complex anatomical pathway that makes it vulnerable to iatrogenic injury during cervical or thoracic surgeries or anesthetic blocks. This study reviewed scientific evidence from the past decade, without language restrictions, using databases such as PubMed and SciELO and search terms including “phrenic nerve paralysis,” “iatrogenesis,” and “neurotization.” The analysis integrated data from prospective studies and systematic reviews, highlighting diagnostic techniques such as dynamic ultrasonography and electroneuromyography. Therapeutic strategies ranged from conservative approaches to surgical interventions, including neurotization with autologous grafts and diaphragmatic plication. The findings conclude that preventing iatrogenic injuries requires standardized protocols, intraoperative monitoring, and equitable access to therapies. These measures are essential to reduce morbidity and mortality and improve clinical outcomes, particularly in vulnerable populations such as the elderly and patients with neuromuscular comorbidities.
Keywords: Depression; antidepressants; pharmaceutical industry; psychiatric drug research; guillain barre syndrome; Chikungunya; Peripheral neuropathies; Arboviruses.; Tibial plateau fracture; anterior cruciate ligament injury; arthroscopic surgery; ligament reconstruction; Metabolically Healthy Obese (MHO); Metabolically Unhealthy Obese (MUO); Night Eating Syndrome; Sleep Pattern; Sugar-Sweetened Beverage.; west bengal; BMI.; Adolescent girls; ultra-processed foods; fat intake; menarche; menstrual health; Statistics; Burundi; Cox Model; Kaplan-Meier Model; Survival Analysis; Neonatal Mortality; fibrosis; Denervation; Atrophy; Hypoventilation; and Neurostimulation.